1991
DOI: 10.1177/0148607191015006637
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized Oxidation of Tryptophan: Effect on Liver and Brain Tryptophan

Abstract: Toxic products are formed when tryptophan is irradiated with light in the presence of photosensitizers such as riboflavin. In order to further investigate this phenomenon, solutions of tryptophan (48 mumol.mL-1) were irradiated with broad spectrum fluorescent light in the presence or absence of riboflavin (0.01 mg.mL-1). Solutions of riboflavin were similarly irradiated; control solutions were the respective solutions not exposed to light. Two-week-old suckling gerbils were then assigned to receiving 7 days of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…Aminosäuren reduzieren bzw. verhindern in Mischlösungen mit Lipidemulsionen oder Multivitaminpräparaten die Peroxidbildung [9], werden hierbei aber oxidiert [16,17]. Die Bildung von Peroxiden in Lipidemulsionen ist bei Raumlicht gering, bei Fototherapielicht erheblich [7].…”
Section: Bewertende Stellungnahmeunclassified
“…Aminosäuren reduzieren bzw. verhindern in Mischlösungen mit Lipidemulsionen oder Multivitaminpräparaten die Peroxidbildung [9], werden hierbei aber oxidiert [16,17]. Die Bildung von Peroxiden in Lipidemulsionen ist bei Raumlicht gering, bei Fototherapielicht erheblich [7].…”
Section: Bewertende Stellungnahmeunclassified
“…These species are further prone to decomposition in presence of redox active metal ions to yield alkoxyl radicals, which can add to the oxidative damage (Cardoso et al, 2012). Detailed investigations have revealed that among all the amino acids, tryptophan is most susceptible to such flavin-sensitized photooxidation in an oxygen-independent mechanism (Bhatia et al, 1991;Silva et al, 1991Silva et al, , 1994Garcia and Silva, 1997;Fuentes-Lemus and Lopez-Alarcon, 2020). Excited state riboflavin binds to tryptophan under a light-induced reaction and leads to cytotoxicities like axonal degeneration and further cascade of photo-adduct formation (Silva et al, 1991;Lucius et al, 1998;Lopez-Alarcon et al, 2014).…”
Section: Flavins As Photosensitizers In the Retinamentioning
confidence: 99%